Low dielectric and low surface free energy flexible linear aliphatic alkoxy core bridged bisphenol cyanate ester based POSS nanocomposites - Alagar, Muthukaruppan; Devaraju, S; Prabunathan, P; Selvi, M (Frontiers in Chemistry, 2013)
The aim of the present work is to develop a new type of flexible linear aliphatic alkoxy core bridged bisphenol cyanate ester (AECE) based POSS nanocomposites for low k applications. The POSS-AECE nanocomposites were developed by incorporating varying weight percentages (0, 5 and 10 wt %) of octakis (dimethylsiloxypropylglycidylether) silsesquioxane (OG-POSS) into cyanate esters. Data from thermal and dielectric studies imply that the POSS reinforced nanocomposite exhibits higher thermal stability and low dielectric value of k=2.4 (10 wt% POSS-AECE4) compared than those of neat AECE. From the contact angle measurement, it is inferred that, the increase in the percentage incorporation of POSS in to AECE, the values of water contact angle was enhanced. Further, the value of surface free energy was lower when compared to that of neat AECE. The molecular level dispersion of POSS into AECE was ascertained from SEM and TEM analyses.